Photophysical Properties and Redox Potentials of Photosensitizers for Organic Photoredox Transformations - Wu, Yanyu; Kim, Dooyoung; Teets, Thomas S. (Synlett, 2021)
Photoredox catalysis has proven to be a powerful tool in synthetic organic chemistry. The rational design of photosensitizers with improved photocatalytic performance constitutes a major advancement in photoredox organic transformations. This review summarizes the fundamental ground-state and excited-state photophysical and electrochemical attributes of molecular photosensitizers, which are important determinants of their photocatalytic reactivity.
Keywords: photosensitizers; photoredox catalysis; redox potentials; excited states; photophysics; photochemistry